NEUROLINGUISTICS PERSPECTIVE ON LEXICAL PERCEPTION AND SEMANTIC DISORDER OF AUTISM SPECTRUM DISORDER - Indah, Rohmani Nur (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Autism patients get suffer from language disorder that can be identified from the late of speaking, the problems in processing linguistic information and understanding the speech meaning. This triggers to the learning problems that is worsened by attention disorder. The language acquisition is also affected by the limited vocabularies, starting from lexical perception up to vocabularies that are parts of semantic acquisition. In neurolinguistics perspective, complexity of language disorder for the spectrum autism can be explained based on the perceptual information management and the domination of his brain hemisphere. Linguistic information is processed in monoprocessing due to different hemisphere domination that happens after the process of brain lateralizes that ends up to the base of different lexicon perceptual system and the semantic acquisition for spectrum autism so that his expressive language skill reaches far beyond his receptive language. This strengthen the argumentation that language pathology is based on the relation between brain and linguistic mechanism.Keywords: Neurolinguistics, Lexical Perception, Semantic Disorder, Autism Spectrum Disorder